Study on the cytocompatibility, mechanical and antimicrobial properties of 3D printed composite scaffolds based on PVA/ Gold nanoparticles (AuNP)/ Ampicillin (AMP) for bone tissue engineering - GÜNDÜZ, OĞUZHAN (ELSEVIER, 2021)
Over the years, gold nanoparticles (AuNP) have been widely used in several biomedical applications related to the diagnosis, drug delivery, bio-imaging, photo-thermal therapy and regenerative medicine, owing to their unique features such as surface plasmon resonance, fluorescence and easy surface functionality. Recent studies showed that gold nanoparticles display positive effect on osteogenic differentiation. In line with this effect, 3-Dimesional (3D) scaffolds that can be used in bone tissue were produced by exploiting the properties of gold nanoparticles that increase biocompatibility and support bone tissue development. In addition, ampicillin was added to the scaffolds containing gold nanoparticles as a model drug to improve its antimicrobial properties. The scaffolds were produced as composites of polyvinyl alcohol (PVA) main matrix as PVA, PVA/AuNP, PVA/Ampicillin (AMP) and PVA/AuNP/AMP. Scanning Electron Microscopy (SEM) Fourier Transform Infrared Spectroscopy (FTIR), tensile measurement tests, and in vitro applications of 3D scaffolds were performed. As depicted by SEM, scaffolds were produced at pore sizes appropriate for bone tissue regeneration. According to FTIR results, there was no modification observed in the AMP, PVA and gold nanoparticles due to mixing in the resultant scaffolds. In vitro results show that 3D printed composite scaffold based on PVA/AuNP/AMP are biocompatible, osteo-inductive and exhibit antimicrobial properties, compared to PVA scaffolds. This study has implications for addressing infections during orthopedic surgeries. The PVA-based gold nanoparticle 3D tissue scaffold study containing ampicillin covers a new study compared to other articles based on gold nanoparticles.
Keywords: Gold nanoparticle; PVA; Ampicillin; 3D printing; Bone tissue engineering; GRAPHENE OXIDE; POLY(VINYL ALCOHOL); RELEASE